Relationship Between HbA1c in 3rd Trimester & Pregnancy Outcome of Patients with Gestational Diabetes Mellitus (GDM) (Central Medical College Journal, 2025)
Background: Gestational Diabetes Mellitus (GDM) is a condition characterized by glucose intolerance with onset or first recognition during pregnancy. It affects approximately 7% of all pregnancies and is primarily associated with increased insulin resistance and inadequate compensatory insulin secretion. GDM poses significant risks for both maternal and neonatal health, including complications such as preeclampsia, macrosomia, neonatal hypoglycemia, and an increased likelihood of developing type 2 diabetes mellitus later in life. Elevated maternal HbA1c levels in the third trimester have been linked to increased risks of complications such as preterm delivery, vulvovaginitis, polyhydramnios, and neonatal issues including hypoglycemia and macrosomia. Monitoring HbA1c levels during pregnancy, alongside blood glucose, may provide valuable insights into managing euglycemia and reducing the risks of these complications. This study aims to evaluate the impact of third-trimester HbA1c levels on pregnancy outcomes, focusing on both maternal and fetal health in women with controlled and uncontrolled serum HbA1c levels. Methods: This cohort-type observational study was conducted at the Department of Gynaecology and Obstetrics, BIRDEM-II General Hospital, Dhaka, from July 2019 to June 2020. The study included pregnant women diagnosed with Gestational Diabetes Mellitus (GDM) attending the outpatient department or admitted to the hospital. Participants were categorized into two groups based on third-trimester HbA1c levels: those with HbA1c >6.0% (uncontrolled group) and those with HbA1c ≤ 6.0% (controlled group). A sample size of 100 was determined by consecutive purposive sampling, with 50 participants in each group. During the third trimester, 5 cc of venous blood was collected from each participant for HbA1c and blood glucose level testing. Participants were monitored for fetomaternal outcomes during the follow-up period, which lasted until the puerperium. Data were collected using a pre-structured form, and the researcher personally gathered all information to ensure accuracy. After data collection, the information was carefully reviewed, and inconsistencies were corrected. Results: This prospective cohort study conducted at BIRDEM-II General Hospital, Dhaka, aimed to investigate the impact of third-trimester HbA1c levels on pregnancy outcomes in Gestational Diabetes Mellitus (GDM) patients. The study included 100 participants, categorized into controlled (HbA1c ≤ 6%) and uncontrolled (HbA1c > 6%) groups. The results demonstrated that poor glycemic control was significantly linked to increased rates of polyhydramnios, preterm delivery, macrosomia, and neonatal complications including hypoglycemia, hyperbilirubinemia, and respiratory distress syndrome (RDS). Additionally, newborns in the poorly controlled group had significantly higher rates of NICU admission, incubator care, and resuscitation at birth. However, there was no significant difference in mode of delivery or maternal complications between the two groups. These findings suggest that poor HbA1c control in the third trimester is linked to adverse maternal and fetal outcomes in GDM pregnancies. Conclusion: The study found that GDM patients with HbA1c >6.0% in the third trimester had higher rates of complications such as polyhydramnios, preterm delivery, macrosomia, hypoglycemia, hyperbilirubinemia, RDS, NICU admissions, incubator care, and resuscitation at birth, compared to those with HbA1c ≤6.0%. However, differences in vulvovaginitis, oligohydramnios, PPH, and UTIs were not statistically significant.Central Medical College Journal Vol 9 No 1 January 2025 Page: 31-36